Asian American Youth : Culture, Identity and Ethnicity. - Lee, Jennifer (Routledge, 2004)
This interdisciplinary volume covers such topics as Asian immigration, acculturation, assimilation, intermarriage, socialization, sexuality, and ethnic identification.